Physical fitness and psychological health in overweight/obese children: A cross-sectional study from the ActiveBrains project. Issue 2 (February 2018) - Rodriguez-Ayllon, M.; Cadenas-Sanchez, C.; Esteban-Cornejo, I.; Migueles, J.H.; Mora-Gonzalez, J.; Henriksson, P.; Martín-Matillas, M.; Mena-Molina, A.; Molina-García, P.; Estévez-López, F.; Enriquez, G.M.; Perales, J.C.; et al.
Abstract: Objectives: To examine the associations of physical fitness (i.e. cardiorespiratory fitness, muscular strength, and speed/agility) with psychological distress and psychological well-being in overweight/obese pre-adolescent children. Design: 110 overweight/obese children (10.0 ± 1.1 years old, 61 boys) from the ActiveBrains project (http://profith.ugr.es/activebrains ) participated in this cross-sectional study. Methods: Physical fitness was evaluated by the ALPHA battery test. Cardiorespiratory fitness was additionally evaluated by a maximal incremental treadmill. Stress was assessed by the Children's Daily Stress Inventory, anxiety by the State-Trait Anxiety Inventory, depression by the Children Depression Inventory, positive affect and negative affect by the Positive and Negative Affect Scale for Children, happiness by the Subjective Happiness Scale, optimism by the Life Orientation Test, and self-esteem by the Rosenberg Self-Esteem questionnaire. Linear regression adjusted for sex and peak height velocity was used to examine associations. Results: Absolute upper-body muscular strength was negatively associated with stress and negative affect ( β = −0.246, p = 0.047; β = −0.329, p = 0.010, respectively). Furthermore, absolute lower-body muscular strength was negatively associated with negative affect ( β = −0.301, p = 0.029). Cardiorespiratory fitness, expressed by the last completed lap, and relative upper-body muscular strength were positively associated with optimism ( β = 0.220, p = 0.042; β = 0.240, p = 0.017, respectively). Finally, absolute upper-body muscular strength was positively associated with self-esteem ( β = 0.362, p = 0.003) independently of sex and weight status (p for interactions >0.3), and absolute lower-body muscular strength was also positively associated with self-esteem ( β = 0.352, p = 0.008). Conclusions: Muscular strength was associated with psychological distress (i.e. stress and negative affect) and psychological well-being (i.e. optimism and self-esteem) as well as cardiorespiratory fitness was associated with optimism. Therefore, increased levels of physical fitness, specifically muscular strength, could have significant benefits for overweight/obese children psychological health.